Faktor-Faktor Yang Mempengaruhi Produksi Kakao Di Indonesia Tahun 2014-2016 - Nurul Izzah (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2016)
Indonesia is the country's third largest cocoa producer in the world. Cocoa plantations developed in the past 20 years but did not followed by an increase in cocoa production. Factors affecting cocoa production including land and labor. Indonesia has the potential to develop cocoa plantations because high world demand for cocoa, but it can also to meet the needs of cocoa in the country. The purpose of this study was to analyze the influence of land and labor on cocoa production. The research was quantitative analytic with data with the panel data obtained from directorate general of plantations. The result of the research showed that there was the positif influence of land area variable to the variable cocoa production. The result of the research also showed that there was the positif influence of labor variable but not significant to the variable cocoa production.